Lifelong Learning: The Role of Libraries - Tackie, Samuel Bekoe (Ghana Library Journal, 2011)
In the history of the World, we have passed through several Ages. There were the Stone Age, Iron Age, Copper Age, Industrial Revolution which may be called The Industrial Age and the Age of Learning of the Renaissance. Then there was The Middle Ages which straddled the end of the ancient world and the beginning of the modern world.